Perioperative safety indicators: surgery cancellation and immediate postoperative complications - Sibéle da Silva; Bruna Kruczewski; Sirlei Fávero Cetolin; Andreia Dalla Vecchia; Vilma Beltrame (Universidade Estadual de Maringá, 2020)
The perioperative period comprises the moments before, during and after surgery. Based on the concern about the care for and safety of patients in this process, this study sought to assess the quality of surgical procedures in a hospital environment. It is an epidemiological, descriptive and retrospective research conducted at Santa Terezinha University Hospital [Hospital Universitário Santa Terezinha], in the municipality of Joaçaba, Santa Catarina (SC). The investigation aimed to identify the reasons for surgical cancellation, as well as immediate postoperative complications that occur in the postanesthesia care unit. A total of 456 records from surgery cancellation daily maps and 361 medical records of patients in postoperative care were analyzed. Results show that the main cause for cancellation of surgeries was transfer or unscheduled procedure (23.1%), but 27% of the unscheduled surgeries did not have the reason for cancellation reported. Adult (over 80%) and female individuals were the majority for both cancelled surgeries and postoperative complications. The most frequent postoperative complication was hypotension. Among performed surgeries, thoracic ones (41.8%) were most prevalent, while abdominal/pelvic (49%) surgeries were the most cancelled.  It is concluded that a big portion of the cancelled surgical procedures could have been prevented, since only 6.8% of them were related to clinical conditions.